GENDER PROFILE OF HEALTHCARE-ASSOCIATED INFECTIONS IN ORAL AND MAXILLOFACIAL SURGERY CLINIC IAȘI (2011-2018) - Magda Călina Bârlean; Monica Mihaela Scutariu; Cosmin Ionuț Crețu; Livia Bobu; Alexandra-Lorina Platon; Andra Tărăboanță-Gamen; Georgiana Macovei (Romanian Society of Oral Rehabilitation, 2023)
The aim of this study was to evaluate the Healthcare Associated Infections (HAI) profile according to the patient's gender in Oral and Maxillo-Facial Surgery Clinic Iași between 2011 and 2018. Material and methods. A retrospective study on HAI between 2011 and 2018 was initiated at the OMF Clinic Iași . SPSS 24 system was used for the statistical analysis of the data.. Results. 231 cases of HAI were diagnosed in a total of 154 patients.. The HAI recorded incidence was twice higher in men compared to women (0,99% and 0,49%, respectively). 72,2% of female patients were hospitalised for tumour pathology. Women were mainly exposed to urinary and digestive infections, while in men the most frequent HAI were the surgical site infections, respiratory infections and infections associated with therapeutic manoeuvres. The discharge status was 63,0% healed, 2,3% stationary, 22,5% improved for male patients and 44,8% healed, 34,5% improved for females. 3,5% men and 10,3% women died. Male patients attended Intensive Care Unit in a significantly higher proportion compared to female patients (66,1%, respectively, 41,7%). Conclusions. The assessment of the patients' gender as a risk factor for HAI is necessary for this pathology surveillance, control and prevention.